The Effect of Good Zakat Governance (GZG) Implementation on Muzakki Satisfaction at the National Amil Zakat Agency (BAZNAS) East Kutai Regency - Bambang Iswanto; Muhammad Riswan; Ashar Ashar; Ibadurrahman Ibadurrahman (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This study aims to determine the effect of accountability, responsibility, transparency, and Fairness on Muzakki satisfaction in Baznas Kutai Timur. This type of research is quantitative, with samples taken by accidental sampling. Data collection techniques include observation, documentation, and questionnaires. Data analysis techniques include validity tests, reliability tests, classical assumption tests, multiple regression tests, and hypothesis tests. The results of this study show that partially, the variables of Accountability, Responsibility, transparency, and Fairness have a significant positive effect on Muzakki satisfaction in Baznas Kutai Timur. Simultaneously, Accountability, Responsibility, transparency, and fairness (justice) have a positive and significant effect on Muzakki satisfaction in Baznas Kutai Timur.Penelitian ini bertujuan untuk mengetahui pengaruh Akuntabilitas, Responsibilitas, Transparansi dan Fairness (keadilan) terhadap kepuasan Muzakki di Baznas Kutai Timur. Adapun jenis penelitian ini adalah penelitian kuantitatif dengan sampel menggunakan accidental sampling. Teknik pengumpulan data berupa observasi, dokumentasi, dan angket. Teknik analisis data yaitu uji validitas, relibilitas, uji asumsi klasik, uji regresi berganda dan uji hipotesis. Hasil penelitian ini menunjukkan bahwa secara parsial variabel Akuntabilitas, Responsibilitas, Transparansi dan Fairness (keadilan) berpengaruh positif signifikan terhadap kepuasan Muzakki di Baznas Kutai Timur. Secara simultan Akuntabilitas, Responsibilitas, Transparansi dan Fairness (keadilan) berpengaruh positif dan signifikan terhadap Kepuasan Muzakki di Baznas Kutai Timur.